Mixed Messages: Validity and Ethics of Facilitated Communication - Stock, Barbara (Disability Studies Quarterly, 2011)
Keywords facilitated communication, autism, developmental disability, ethics Abstract I identify several factors that influence how significant mediation is for an instance of communication: dependability, accuracy, neutrality, control of output, and access to feedback. Then, I use this conceptual framework to discuss Facilitated Communication, a controversial method for communicating with people with autism or other developmental disabilities. After reviewing the history of this method, I try to assess whether it is valid and whether it is ethical by setting up and evaluating arguments offered on either side of the debate. My conclusion is that Facilitated Communication has not been shown to be valid, but that it may, under some conditions, be ethically acceptable.